2008
DOI: 10.1016/j.pneurobio.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Are numbers special? An overview of chronometric, neuroimaging, developmental and comparative studies of magnitude representation

Abstract: There is a current debate whether the human brain possesses a shared representation for various types of magnitude such as numerical quantities, physical size, or loudness. Here, we critically review evidence from chronometric, neuroimaging, developmental and comparative fields, and supplement it with a meta-analysis of the neuroimaging data. Together, based on such an integrative overview, we discuss limitations inherent in each approach, and the possibility whether shared, or distinct magnitude representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
304
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(353 citation statements)
references
References 153 publications
32
304
1
7
Order By: Relevance
“…Current theories of dyscalculia include specific deficits of the ANS, that is, imprecise representations of nonsymbolic number (18), or specific deficits in mapping symbols to nonsymbolic number representations (68). These and other theories (17) have been silent about how nonsymbolic magnitudes other than number are represented in the brains of children and adults, and by extension, how a system of general magnitude representation, which includes nonnumerical magnitudes such as spatial extent and duration (69)(70)(71), might interface with learning and competence across different types of mathematical problem solving. Dyscalculia and other math-related disorders such as acalculia are heterogeneous in their symptomatology (15,72).…”
Section: Discussionmentioning
confidence: 99%
“…Current theories of dyscalculia include specific deficits of the ANS, that is, imprecise representations of nonsymbolic number (18), or specific deficits in mapping symbols to nonsymbolic number representations (68). These and other theories (17) have been silent about how nonsymbolic magnitudes other than number are represented in the brains of children and adults, and by extension, how a system of general magnitude representation, which includes nonnumerical magnitudes such as spatial extent and duration (69)(70)(71), might interface with learning and competence across different types of mathematical problem solving. Dyscalculia and other math-related disorders such as acalculia are heterogeneous in their symptomatology (15,72).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, functional neuroimaging reveals that representations of these dimensions engage overlapping or neighboring regions of posterior parietal cortex (Cohen Kadosh et al, 2005, 2007; V. Dormal, Dormal, Joassin, & Pesenti, 2011;Fias, Lammertyn, Reynvoet, Dupont, & Orban, 2003). These findings provide mechanistic support for the many studies that have documented behavioral and neurological links between representations of space, time, and number (Allman, Pelphrey, & Meck, 2012;Cantlon et al, 2009;Cohen Kadosh, Lammertyn, & Izard, 2008;Feigenson, 2007;Hubbard et al, 2005;Walsh, 2003). However, implicit in ATOM is the idea that the links between different dimensions should be symmetrical.…”
mentioning
confidence: 93%
“…First, patients with parietal lesions consistently show selective impairments in numerical skills (e.g., Dehaene and Cohen, 1997;Denes and Signorini, 2001;Grafman et al, 1982;Takayama et al, 1994;Warrington, 1982;Zorzi et al, 2002), whereas patients with lesions to other brain regions showed preservation of numerical skills (e.g., Butterworth et al, 2001;Cappelletti et al, 2001Cappelletti et al, , 2002Cappelletti et al, , 2005Crutch and Warrington, 2002;Diesfeldt, 1993;Jefferies et al, 2004Jefferies et al, , 2005Lemer et al, 2003;Zamarian et al, 2006). Second, functional MRI studies have systematically shown that numerical processing elicits greater activation in the parietal lobule than does nonnumerical processing (e.g., Ansari et al, 2006;Cappelletti et al, 2010;Eger et al, 2003;Knops et al, 2006;Le Clec'H et al, 2000;Piazza et al, 2004;Thioux et al, 2005;Zago et al, 2008; but see Göbel et al, 2004;Kadosh et al, 2008;Shuman and Kanwisher, 2004). Third, developmental dyscalculia has also been showed to be associated with structural abnormalities in the IPS regions (e.g., Isaacs et al, 2001;Kucian et al, 2006;Molko et al, 2003Molko et al, , 2004Rotzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%